The Relationship Between Philanthropic Attitude and Economic Jihad in the Muslim Community - Mohamad Sabri Haron; Radin Anis Adlina Radin Hasbani; Syaidatun Nazirah Abu Zahrin; Aminudin Basir; Shofian Ahmad; Salmy Edawaty Yaacob; Azizi Umar; Nor Huda Md. Anuar (USIM Press, 2024)
JMIFR Vol.18 No.1 (June) 2021